Oxidative Stress & FoxO Transcription Factors in Cardiovascular Aging - Kim, Juewon; Y. Cho, Si; Cho, Donghyun; H. Kim, Su; B. Seo, Dae; S. Shin, Song (Current Medicinal Chemistry, 2017)
Background: Aging is a phenomenon in which the functions, adaptability and resistance of an organism decrease over time. With the global population aging at an accelerating pace, delaying the negative aspects of aging is vital for advancing the human life span and quality of life. The aging of multiple organs can lead to many diseases, and the cardiovascular system is no exception. Indeed, one of the primary risk factors for cardiovascular diseases is aging because of altered cardiovascular metabolism resulting in metabolic disorders and inflammation. Methods: We attempted an organized search of bibliographic databases for peer-reviewed research papers by searching featured reviews using inclusion/exclusion criteria. The collected papers were assessed by standard tools for quality control. Results: Forty-six papers were admitted to the review, and most papers featured recent research results (44) and reviewed the research field (8). We discuss these papers along with the recent progress of our work. In this review, we examine the relationship of oxidative stress with aging and the FoxO proteins, which are essential anti-aging factors in the cardiovascular system. Conclusion: The observations of this review suggest that anti-aging signaling mediated by FoxO proteins is important for understanding cardiovascular aging and the design of medicinal approaches.
Keywords: Aging